2003
DOI: 10.1136/pmj.79.937.652
|View full text |Cite
|
Sign up to set email alerts
|

Completion of the audit cycle: standardised nurse-led information for patients

Abstract: Background: It is increasingly accepted that patients want information about their proposed treatment, and that provision of such information may alleviate fear and may improve the process of obtaining informed consent. It is not yet clear what form such information should take. Objective: Based on differences shown previously between patients receiving standard treatment and those in clinical trials, a system of routine appointments with a chemotherapy nurse at least one day before the patient offered consent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…It has been identified that overwhelming the patient with information could potentially lead to confusion, and unnecessary anxiety for the patient and their families (McCaughan & Thompson 2000), as was believed by some of the participants. A further consideration, evident in this study, and supported by others was patients needed time to digest information before consenting to the treatment (McCaughan & Thompson 2000; Sharma et al . 2003).…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…It has been identified that overwhelming the patient with information could potentially lead to confusion, and unnecessary anxiety for the patient and their families (McCaughan & Thompson 2000), as was believed by some of the participants. A further consideration, evident in this study, and supported by others was patients needed time to digest information before consenting to the treatment (McCaughan & Thompson 2000; Sharma et al . 2003).…”
Section: Discussionsupporting
confidence: 54%
“…Providing information to patients to enable them to make informed decisions is a complex process, made more so in the diagnosis of cancer where statistics about survival and low probabilities of response to treatment are combined with consideration of the potential toxicity of chemotherapy, and need to be addressed within discussions with patients (Sharma et al . 2003).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations